The Impact of Applying Augmented Reality Technology in Learning on Student Learning Experiences - Meriyati Meriyati; Mahon Nitin; Snyder Bradford; Vandan Wiliyanti (Yayasan Adra Karima Hubbi, 2024)
Background:Augmented Reality AR technology is a technology that combines information from the real world with computer technology, so that the learning process can provide varied learning experiences to students. Research purposes:This research was conducted with the aim of understanding the impact of applying Augmented Reality technology in learning on students' learning experiences. Apart from that, to be able to find out the impact of applying Augmented Reality technology to make learning more interesting for students, the use of Augmented Reality can help teachers and parents learn. Method:The method used in this research is a quantitative method.This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. Results:From this research, researchers were able to obtain research results on the impact of applying Augmented Reality technology in learning, showing that using Augmented Reality technology as a learning medium greatly facilitates learning and has the ability to change the way students think. In addition, by using Augmented Reality Technology in Learning, teachers can facilitate the exchange of information between recipients and senders or educators and students. Conclusion:Based on the results of this research, it can be concluded that the impact of applying Augmented Reality Technology in Learning on Student Learning Experiences has a number of quite large benefits, such as providing an immersive learning experience, an interesting learning environment, and an easier learning process. Apart from that, the application of Augmented Reality Technology can also make learning more fun, increase students' interest and desire to learn, and increase students' interest in learning.